A controlled clinical crossover trial of exercise training to improve cognition and neural communication in pediatric brain tumor survivors. Issue 7 (July 2020) - Cox, Elizabeth; Bells, Sonya; Timmons, Brian W.; Laughlin, Suzanne; Bouffet, Eric; de Medeiros, Cynthia; Beera, Kiran; Harasym, Diana; Mabbott, Donald J.
Highlights: Pediatric brain tumor survivors (PBTS) engaged in 12 weeks of aerobic exercise training. PBTS demonstrated increased attentional control after exercise training. Exercise training predicted changes in theta and alpha phase coherence in PBTS. Abstract: Objective: To assess the efficacy of aerobic exercise training to improve controlled attention, information processing speed and neural communication during increasing task load and rest in pediatric brain tumor survivors (PBTS) treated with cranial radiation. Methods: Participants completed visual-motor Go and Go/No-Go tasks during magnetoencephalography recording prior to and following the completion of 12-weeks of exercise training. Exercise-related changes in response accuracy and visual-motor latency were evaluated with Linear Mixed models. The Phase Lag Index (PLI) was used to estimate functional connectivity during task performance and rest. Changes in PLI values after exercise training were assessed using Partial Least Squares analysis. Results: Exercise training predicted sustained (12-weeks) improvement in response accuracy ( p <0.05) during No-Go trials. Altered functional connectivity was detected in theta (4–7Hz) alpha (8–12Hz) and high gamma (60–100Hz) frequency bands ( p <0.001) during Go and Go/No-Go trials. Significant changes in response latency and resting state connectivity were not detected. Conclusion: These findings support the efficacy of aerobic exercise to improve controlled attention and enhance functional mechanisms under increasing task load in participants. Significance: It may be possible to harness the beneficial effects of exercise as therapy to promote cognitive recovery and enhance brain function in PBTS.